Internal Communication in Creating Performance Synergrity - Meiby Zulfikar; Putri Handayani; Achmad Nasrudin; Defika Lailatul; Olivia Putri Andini (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2023)
In supporting the quality of human life, it continues to develop and carry out communication activities. Communication activities have an important role for anyone who runs them. Communication activities within the organization also support the process of employee synergy. In the organizational communication order, communication patterns are used to achieve the same organizational communication goals, from what has been mutually agreed upon. Internal communication is a communication process that runs for each individual, determining the quality of performance for the individual within it.